Down's syndrome with a recombinant tandem duplication of chromosome 21 derived from a maternal ring. Issue 4 (August 1984) - Howell, R T; McDermott, A; Gardner, A; Dickinson, V
Abstract : An account is given of the cytogenetic investigations of a girl with Down's syndrome found to have a dicentric duplication of chromosome 21. This tandem type of rearrangement was interpreted as a recombinant derived from a single meiotic crossover between a maternal ring 21 and its normal homologue. A population of cells was also found in which breakage of the dicentric resulted in a chromosome 21 with a small terminal deletion. The mother and the proband's younger brother, who was also a ring 21 heterozygote, were both clinically normal.